(3JLQjO GdYfGjI aj JMQjQ CMcGe GdfgGjIs - (3Ydj Hf YHGS GdjYdj GdMfHdis; (3eMahX Hf CMeO Hf GdMSf GdcdhPGfj, CHh GdNWGH,J (B510 (3g` s
(3ChdgG (B:s
(3CeG HYO , aEf GdTjN GdEeGe GdYGde CHG GdaQL YHO GdQMef Hf QRjf ef TgOGA OGQ GdSdGe s
(3BNQgG (B:s
(3Ef bGd de jcf edci Je edcJg HYO bHd HjfI eGde jcPHgG HCf cGf bO CbQ Gfg edcg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B291 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B188s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B(904) s
Keywords: (3Gdabg GdMfHdjs